Framing Water–Energy–Food–Ecosystem (WEFE) nexus interactions in the Tana-Beles Sub-Basin of Ethiopia - Abera, Wuletawu; Getaneh, Yonas; Balcha, Yodit; Assefa, Tewodros; Mulatu, Chalachew A.; Ebrahim, Girma Yimer; Tesfaye, Megersa; Dawit, Meseret; Abebe, Wubneh Belete; Taye, Meron Teferi (Springer, 2024)
The water–energy–food–ecosystems (WEFE) provide vital resources that are essential to human existence. Exploring synergies and trade-offs in these systems has been of interest in recent years to increase economic gain while sustaining the environment. The Tana-Beles Sub-basin of Ethiopia is challenged by population density, climate change, and ecosystem degradation that requires a WEFE Nexus thinking. To understand the current WEFE nexus interactions in the basin, a systematic review of 102 scientific research articles published from 1991 to 2021 was undertaken. Additionally, the systematic review is complemented by spatial data analysis to identify synergies and trade-offs among the WEFE nexus indicators. The analysis revealed the dominance of food–water–ecosystem interdependencies in WEFE nexus research for the Tana-Beles Sub-basin. This dominance is driven by extensive food production activities, which lead to substantial water abstraction and hydrological alterations to meet the intensive water demands of crop cultivation. Simultaneously, the energy-ecosystem interactions are critical due to excessive biomass utilization that exceeds the biomass production potential of the area. Furthermore, the available vegetation cover of the area is very limited to supplement the growing fuel wood demands, which is exerting extreme land degradation and threatening the ecosystem in the sub-basin. This study identifies gaps in WEFE understanding, highlights specific challenges and opportunities within the basin, and calls for coordinated stakeholder action for sustainable resource management through a Nexus approach.